Transformation of transport accessibility and tourism development in Todzhinsky kozhuun of the Republic of Tuva - Kuklina, Maria V.; Krasnoshtanova, Natalia E.; Dirin, Denis A.; Bogdanov, Victor N.; Trufanov, Andrey I. (The New Research of Tuva, 2024)
The article reveals the patterns of social processes in the interactions and mutual influence influences between the development of tourism, transport infrastructure and the local community in the Todzhinsky kozhuun of the Republic of Tuva. Interest in this territory is due to significant changes associated with completion of the Kyzyl — Toora-Khem Road in 2009 and the recent opening of the bridge connecting the banks of the Great Yenisei in 2022. Various details of the study were established using a set of sociological and statistical methods. Also, during the study, the attitude of society to the ongoing changes in the field under consideration was recorded. The actual problem lies in the fact that contradictions often arise between the participants involved in the process of implementation of territorial and sectoral development plans. Possible disagreement is conditioned by multidirectional interests (individual and group) of multiple representatives of different parties. Characteristic contradictions are manifested in the attitude of the indigenous population of remote territories to the development of tourism. The authors identified a number of populations with diverse interests with diverse interests, demonstrating different attitudes to the problem being covered: representatives of the administration — both with optimism and the prospect of economic development, and with additional preventive work; representatives of public sector institutions and pensioners — with caution, but understanding greater accessibility to medical and educational services; representatives of organizations directly or indirectly related to the service of tourists — with the possibility of obtaining additional income; representatives of organizations not related to tourism — the population is neutral without competition; those not related to tourism are twofold, contradictory, with an understanding of both the advantages in the development of transport links and the disadvantages of the impact on the cultural and natural environment.